PENGENALAN USAHA BUDIDAYA DAN PENGOLAHAN JAMUR TIRAM PUTIH BAGI KELOMPOK EKOWISATA ISYO HILLS KAMPUNG RHEPANG MUAIF, NIMBOKRANG, JAYAPURA - Suharno Suharno; Rosye H.R. Tanjung (LPPM Uncen, 2018)
Promoting fungi as food is necessary, especially for the community in Papua. Papua has abundant natural resources, including fungi diversity that can be consumed. Cultivation and propagation of mushrooms is not yet known because of limited knowledge. The purpose of this activity is to provide learning for the community about the cultivation and processing of various white oyster fungi products (Pleurotus ostreatus) for the Isyo Hills ecotourism group in the Rhepang Muaif Village, Nimbokrang District, Jayapura Regency. The results of the activity showed that there was an increase in public knowledge in the use of white oyster fungi in the cultivation and processing of foodstuffs from fungi. As much as 95.5% of people have heard and seen the fungi consumed by the community, even 9.1% have consumed fungi which are sold in modern stores (supermarkets). Nevertheless, 100% of the people do not know how to cultivate fungi, including P. ostreatus. In fact, of the 12 fungi processing participants were known to be able to create a variety of food ingredients which are made from white oyster fungi. Keywords: food ingredients, cultivation, Oyster fungi, utilization, Rhepang Muaif